Computational study of the structural properties of recycled low-density polyethylene. (15th February 2022) - Yaghini, Nazila; Tuinier, Remco; den Doelder, Jaap
Abstract: We present a comprehensive model to computationally study molecular structure development in the recycling extrusion process of low-density polyethylene (LDPE) and provide initial results versus reported experiments as guidance. Molecular weight distribution (MWD) and branching distribution (BD) are modeled by applying a combination of population balance modeling, the method of moments and branching pseudo distributions. Special cares have been taken to incorporate the effects of scission and crosslinking reactions. Further, effective strategies have been provided to mitigate the computational complexity of solving balance equations. The models have been applied to the case of increasing residence time in a recycling extruder. The simulated MWD of the recycled LDPE exhibits a shift towards lower chain lengths for residence times up to 400 s, while for higher residence times the high MW tail forms. The evolution of the simulated BD during recycling reveals important modifications versus the original virgin LDPE with implications for derived properties. Graphical abstract: Image 1 Highlights: Scission and crosslinking reactions are thermally initiated in recycling processes. Scission and crosslinking reactions degrade polymers in recycling. Population balance modeling reveals the structural changes in recycled polymers. Extruder residence time plays an important role in degradation of recycled polymers.